The Effectiveness of Penta Helix Collaboration In Overcoming The Stagnation of Tourism Village Development: A Case Study of Cirorek Tourism, Karyamekar Village, Garut Regency - Sumarna, Eeng; Geohansa, Ahmad; Kania, Ikeu (Jurnal Toursci, 2025)
Background. The development of tourist villages in Indonesia, especially in Garut Regency, often faces stagnation despite the implementation of various collaborative approaches. Aims. This study aims to evaluate the effectiveness of the Penta Helix model collaboration in overcoming the stagnation of the development of Cirorek tourism village in Karyamekar Village, Garut Regency. Methods. The research method uses a qualitative approach with data collection techniques through observation, interviews, and FGD with key informants of the five leading actors of Penta Helix: the government, the community, academics, business actors, and the media. Result. The results indicate that there is still a weak synergy between actors, limited institutional capacity, and less optimal promotional strategies. Conclusion. An adaptive collaboration model rooted in local cultural values is needed to support the sustainability of village tourism.